A novel technique of cryodenervation for murine vagus nerve: implications for acute lung inflammation - Di Wu; Ximing Liao; Jing Gao; Kun Wang; Wujian Xu; Feilong Wang; Zhixian Jin; Dandan Wu; Qiang Li; Wei Gao (Respiratory Research)
Abstract Background Neuroimmune interaction is an underestimated mechanism for lung diseases, and cryoablation is a competitive advantageous technique than other non-pharmacologic interventions for peripheral nerve innervating the lung. However, a lack of cryodenervation model in laboratory rodents leads to the obscure mechanisms for techniques used in clinic. Method Herein, we developed a novel practical method for mouse peripheral nerve cryoablation, named visualized and simple cryodenervation (VSCD). We first estimated the feasibility, safety and effectiveness of the technique via haematoxylin-eosin staining, histochemistry or immunofluorescence staining and immunoblotting assay. We then constructed the acute lung injury (ALI) model triggered by lipopolysaccharide (LPS) to verify the effect of VSCD in the resolution of pulmonary inflammation. Besides, the IL-10 knockout mice were also applied to explain the underlying mechanism of the protective activity of VSCD in ALI mice. Result We demonstrated that VSCD was able to induce a reliable and stable blockade of innervation, but reversible structural damage of mouse vagus nerve without detectable toxicity to lung tissues. Cholinergic parasympathetic nerve in the mouse lung coming from vagus nerve was activated at the initial stage (1 week) after VSCD, and blocked 3 weeks later. By use of the ALI mouse model, we found that VSCD effectively decreased pulmonary inflammation and tissue damage in the ALI mice. Moreover, the activated cholinergic anti-inflammatory pathway (CAP) and elevated IL-10 expression might explain the protective action of VSCD following LPS challenge. Conclusion This study fills the gap in the cryoablation for mouse vagus nerve, thereby guiding the application of cryodenervation in clinical management of pulmonary diseases. It also offers evidence of anti-inflammatory potential of VSCD in ALI mouse model and opens therapeutic avenues for the intervention of acute lung inflammation.